IMPACT OF LEGAL ENFORCEMENT ON THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND CORPORATE PERFORMANCE - De Luca, Vanessa Mendes; Góis, Alan Diógenes; De Luca, Márcia Martins Mendes; Medeiros, Jislene Trindade (Advances in Scientific and Applied Accounting, 2021)
Objective: To evaluate the impact of legal enforcement on the relationship between corporate governance and corporate performance. Method: The sample consisted of 4,447 public firms (24,025 observations) from 61 countries, for which data covering the period 2010-2018 were available in the databases of Thomson Reuters Eikon and the World Bank. In addition to descriptive statistics and correlation analysis, regressions on panel data were used to determine the effect of law enforcement on the relationship between corporate governance and corporate performance. Results/Discussion: The results showed that the country’s law enforcement should be considered when evaluating the impact of corporate governance mechanisms on corporate performance of public firms, since the results indicated that firms headquartered in countries with efficient law enforcement are engaged in higher levels of corporate governance that result in better corporate performance. Contributions: The study highlights the relevance of law enforcement to research on corporate governance, by presenting thus, evidence that law enforcement, by promoting better corporate governance strategies, contributes to reducing agency conflicts between agent and principal, resulting in better corporate performance. Therefore, managers and policy makers looking to adopt new corporate governance strategies need to take in account the impact of law enforcement. The adoption of corporate governance practices may not produce the expected effects in countries with weak law enforcement.